Pengaruh Jumlah Lintasan Terhadap Tebal, Berat Isi, Stabilitas Dan Kelelahan Lapisan Tipis Aspal Beton Untuk Jalan Raya - ,, Marjono (Prokons: Jurnal Teknik Sipil, 2013)
This Flexible pavement is commonly used on highway construction doe to its advantages, one of them is the flexibility of its mixture concrete asphalt thin layer (LATASTON) is most commonly used are cover layer of highway construction. In its implementation thin material requires a good implementation process, especially in spreading and compacting phases. Otherwise, it will result in declining service age. The research aims at analyzing the influence of passing numbers to the depth, content weight, stability and flow of the LATASTON, experimental model-making road pavement model comprising 3 different passing numbers was employed. fisrtly, compaction with 4 passes, followed by 8 passes in the second, and last was compaction with 12 passes. The anlysis show that passes are influental to the values of LATASTON depth, content weight, stability, and flow. The correlations beetwen passing number and depth Y = 0,006 X2 - 0,156 X + 4,980, correlations beetwen passing number and content weight  Y = 0,112 X2 - 1,039 X + 999,2 correlations beetwen passing number and stability  Y = 2,924 X2 - 20,64 X + 134,7  correlations beetwen passing number and flow  Y = 0,011 X2 - 0,023 X + 3,231   Keywords: flexible pavement; LATASTON; compaction; passing numbers.